Cities and the Super-Rich : Real Estate, Elite Practices and Urban Political Economies - Forrest, Ray; Koh, Sin Yee; Wissink, Bart (The Contemporary City, 2017)
With the rise of wealth inequalities, our cities are changing dramatically. This collection critically engages with and advances existing debates on the super-rich and their roles in these transformations. An interdisciplinary range of contributions from international experts including sociologists, geographers, historians, discourse analysts, and urban studies specialists reveal crucial aspects of the real estate investment practices of the super-rich, their social spaces in the city as well as the distinct influence of the super-rich on the transformation of four key cities: London, Tokyo, Singapore and Hong Kong. By drawing together diverse disciplines, perspectives, and experiences across different geographical contexts, this book offers a fresh, comparative, and nuanced take on the super-rich and the 1% city, as well as a solid, empirically and theoretically grounded basis to think about future research questions and policy implications.- Resumé vydavatel